Hip preservation surgery and the acetabular fossa - Slullitel, Pablo A.; Coutu, Daniel; Buttaro, Martin A.; Beaule, Paul Edgar; Grammatopoulos, George (Université d'Ottawa | University of Ottawa, 2020)
As our understanding of hip function and disease improves, it is evident that the acetabular fossa has received little attention, despite it comprising over half of the acetabulum's surface area and showing the first signs of degeneration. The fossa's function is expected to be more than augmenting static stability with the ligamentum teres and being a templating landmark in arthroplasty. Indeed, the fossa, which is almost mature at 16 weeks of intrauterine development, plays a key role in hip development, enabling its nutrition through vascularization and synovial fluid, as well as the influx of chondrogenic stem/progenitor cells that build articular cartilage. The pulvinar, a fibrofatty tissue in the fossa, has the same developmental origin as the synovium and articular cartilage and is a biologically active area. Its unique anatomy allows for homogeneous distribution of the axial loads into the joint. It is composed of intra-articular adipose tissue (IAAT), which has adipocytes, fibroblasts, leucocytes, and abundant mast cells, which participate in the inflammatory cascade after an insult to the joint. Hence, the fossa and pulvinar should be considered in decision-making and surgical outcomes in hip preservation surgery, not only for their size, shape, and extent, but also for their biological capacity as a source of cytokines, immune cells, and chondrogenic stem cells. Cite this article: Bone Joint Res 2020;9(12):857-869.
Keywords: Acetabular fossa; Acetabulum; Hip joint; Intra-articular adipose tissue; Ligamentum teres